Successful Corticosteroid Treatment of Refractory Spontaneous Vasoconstriction of Extracranial Internal Carotid and Coronary Arteries. Issue 4 (July 2016) - Takeuchi, Mariko; Saito, Kozue; Kajimoto, Katsufumi; Nagatsuka, Kazuyuki
Abstract : Introduction: Spontaneous vasoconstriction of the extracranial internal carotid artery (SVEICA) is a rare cause of cerebral infarction. Most patients with SVEICA suffer recurrent attacks of vasoconstriction. The standard treatment for this condition has not been established and its long-term prognosis is unclear. Case Report: A 25-year-old man with a history of refractory vasospasm angina presented with transient alternating hemiplegia in both the right and left side. Serial carotid ultrasonography examinations showed severe transient stenosis or occlusion of cervical internal carotid arteries on 1 or both sides, with and without neurological symptoms. This condition resolved completely within 1 day to 1 week. The patient did not present any other risk factors for atherosclerosis and was diagnosed with SVEICA. The treatment with calcium antagonists and nitrates did not prevent the attacks. Administration of a corticosteroid substantially reduced the vasospasm attacks. Conclusions: SVEICA is intractable and difficult to diagnose. It has been reported that SVEICA sometimes complicates coronary artery disease, as observed in this case. The present case demonstrated the effectiveness of corticosteroid treatment against this disease. Serial ultrasonography examinations helped us to diagnose and follow-up the vasospasm attacks.